The Role of Marae in Tertiary Education Institutions - Ka’ai, Tania (Te Kaharoa, 2008)
This article explores the notion of the role of a marae in tertiary education institutions, from the experience of advocating for a new building for what was initially simply Maori Studies at Otago, which is the primary case study used in this analysis. Issues of the growth and expansion of the programmes, and the cultural argument for the type of space staff wanted and required to deliver their programmes more effectively are explored, as is the consideration of educating the broader staff network in a tertiary institution for the requirement for such a facility.